Parasocial relationship as a social-cognitive pathway in influencer marketing: evidence from Indonesian beauty followers - Muhmin, Andi Hidayat; Syah, Tantri Yanuar Rahmat; Anggraeni, Adilla (Frontiers in Communication, 2026)
BackgroundSocial media influencers shape consumer decision-making through relational pathways, yet evidence remains mixed on how credibility cues translate into parasocial bonding and purchase intention in emerging markets. Drawing on Source Credibility Theory and the parasocial relationship framework, this study examines the roles of expertise, trustworthiness, and attractiveness in predicting parasocial relationship and purchase intention, while assessing persuasion knowledge as a cognitive mechanism and self-discrepancy as a boundary condition.MethodsSurvey data were collected from 407 Indonesian beauty-influencer followers and analyzed using PLS-SEM with bootstrapping. Direct, indirect, and interaction effects were tested, and out-of-sample predictive relevance was assessed using PLSpredict.ResultsExpertise and trustworthiness were positively associated with parasocial relationship, whereas attractiveness did not predict parasocial relationship but remained positively related to purchase intention. Parasocial relationship was positively related to purchase intention. Persuasion knowledge showed a small but significant direct association with purchase intention; however, the specific indirect effect PSR → PK → purchase intention was not supported at α = 0.05. Self-discrepancy did not moderate the credibility-to-parasocial relationship links. PLSpredict indicated positive out-of-sample predictive relevance for all endogenous constructs.ConclusionThese findings clarify the non-uniform roles of credibility cues in parasocial bonding and inform influencer selection and endorsement transparency in emerging digital markets.